Pengaruh Pengeluaran Pembangunan Terhadap Perekonomian Kabupaten Majalengka - Jaka Sriyana; Fitri Rosyidah (Universitas Islam Indonesia, 2007)
This paper focusses on fiscal policy practice in local government. This research attempts to analyze the impact of government spending for education, health and infrastructure to regional gross domestic product in Kabupaten Majalengka for the period of 1988-2004. We used simple linear regression to test the relationship between independent variabels and dependent variable. In this research, we try to adopt the Skiner (1987). The result of analysis shows that all independent variables, namely government sepnding for educa- tion, health and infrastructure, are statistically significant influence the dependent vari- able. The implications of this finding is that the level of income is strongly depend on local government activities. Kaywords: Fiscal, Government, Policy, Spending